POLA KOMUNIKASI KELUARGA DALAM PENCEGAHAN PERNIKAHAN DINI PASCA BENCANA - Ulmuddin, Ulmuddin; Jabir, Idris (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 18 No 1 (2022)DO - 10.24239/al-mishbah.Vol18.Iss1.255, 2022)
Central Sulawesi is a country that is very prone to natural disasters, while at the same time facing a high prevalence of child marriage. Many studies show that in times of humanitarian crisis, the practice of early child marriage greatly affects the increase in the number of child marriages. This study intends to examine the relationship between natural disasters and child marriage in Central Sulawesi. The results showed that natural disasters were positively related to the likelihood of girls entering child marriage. Child marriage can be an option for households to reduce the burden when they face the adverse welfare effects of natural disasters. Family communication patterns also reduce the number of early marriages. Of the five models of family communication, the role of parents as educators, role models and friends, counselors, and communicators is considered effective to prevent early marriage rates. The strong relationship between child marriage and natural disasters should attract the attention of policymakers to carry out better disaster mitigation programs, as well as to effectively provide assistance to the most vulnerable members of society when natural disasters occur.